Analysis of epidemic trends and status of schistosomiasis in Jiangxi Province from 2002 to 2021 - LI Yifeng; LI Zongguang; HE Tingting; XIE Jingzi; LYU Shangbiao; YUAN Min; LIN Dandan (Shanghai yufang yixue, 2023)
ObjectiveTo analyze the epidemic trends and current status in the prevalence of schistosomiasis in Jiangxi Province from 2002 to 2021， and to provide evidence for formulating and optimizing schistosomiasis control strategies in the province.MethodsEpidemiological data of schistosomiasis in Jiangxi Province from 2002 to 2021 were collected. The Joinpoint regression model was used to investigate the epidemic trends of schistosomiasis， and the annual average percent change （AAPC） was used to assess the changing trend of schistosomiasis infection in humans and bovines. SPSS 25.0 software was used to analyze the target achievement status， infection rate of schistosomiasis in humans and the areas with snails in 2021 to evaluate the differences among various districts and epidemic regions.ResultsBy 2021， 24 counties （61.50%） in the province had achieved the elimination goal， with hilly and marsh counties reaching 82.60% and 31.30%， respectively. The seropositive rate of schistosomiasis in human was 3.51% across the province. However， the seropositive rate in marshland areas （4.77%） was significantly higher than that in hilly areas （1.23 %） （χ2=3 827.51， P<0.001）. The total area with snails in the province was 84 938.32 hm2， including 82 196.86 hm2 in marshland areas and 2 741.46 hm2 in hilly areas. From 2002 to 2021， the infection rate of schistosomiasis in the humans and bovines exhibited a declining trend， with AAPC values of -48.70 and -39.70， respectively. The decline rate in the hilly areas was higher than that in marshland areas. However， the area with snail showed an upward trend （AAPC=0.50）， with a growth rate of 5.80% in hilly areas， which was greater than that in marshland areas （0.40%）.ConclusionFrom 2002 to 2021， the infection rate of schistosomiasis in humans and bovines in Jiangxi Province continued to decline， while the areas with snails increased. The prevention focus should still be on the marshland endemic areas， and attention should also be given to the risk of schistosomiasis in hilly endemic areas. Therefore， it is necessary to continue implementing a comprehensive prevention and control strategy that emphasizes controlling the sources of infection and adopts tailored measures based on local conditions and precise policies.